BAKER’S TRANSLATION STRATEGY ON GOD AND SELF-RELATED WORDS AND EXPRESSIONS IN THE ALCHEMY OF HAPPINESS - Inayah Ahyana R (Journey: Journal of English Language and Pedagogy, 2023)
Certain expressions related to something intangible may be difficult to translate and need special translation strategy. The study’s objective is to classify the strategies conducted by translators to translate SL to TL of God and Self-related words and Expressions from English into Indonesian. This research can be a reference for future research on the topic of translation, especially in the discussion of words or above words and expressions. Furthermore, it is insightful research for readers of this research as well as readers of the book to gain some knowledge in translation terms. This qualitative study compares Indonesian and English versions of the book The Alchemy of Happiness. The Indonesianversion is translated by Haidar Bagir and the English is the work of Claud field. The results revealed that there were 209 data found.The translation strategies used come from Baker (1992). However, only 3 out of 4 were found in the data. The most strategy used weretranslation using similar meaning and form with 102 data (48,80%) and the least was translation by paraphrasing with only 27 data (12,92%). The findings show that the translation using similar meaning and form is a functional strategy to translate the God and self-related words and expressions. Moreover, this study has pedagogical implications for translators in general, translators of God-related texts, as well as students and teachers of translation.